Using experimental de-worming to measure the immunological and pathological impacts of lungworm infection in cane toads. Issue 3 (December 2017) - Finnerty, Patrick B.; Shilton, Catherine M.; Shine, Richard; Brown, Gregory P.
Abstract: The immunological and pathological consequences of parasite infection can be more rigorously assessed from experimental manipulation than from correlational studies of natural infections. We used anthelmintic treatment to experimentally decrease intensities of lungworm infection in captive and free-ranging wild cane toads to assess parasite impacts on host immune responses. First, we administered the anthelmintic drug Ivermectin to both infected and uninfected toads, to distinguish drug effects per se from the impacts of killing lungworms. Worms began dying and decomposing <48 h after injection. The only immunological variables that were affected by anthelmintic treatment were bactericidal capacity of the blood which increased in parasitized toads (presumably triggered by decomposing worms in the lungs), and the phagocytic capacity of blood (which increased in both infected and uninfected toads); the latter effect presumably was caused by the injection of Ivermectin per se rather than removal of parasites. Second, we looked at correlates of variation in the infection intensity induced by de-worming (in both captive and free-ranging toads) over an eight-week period. Heavier lungworm infection was associated with increased phagocytic ability of the host's blood, and a reduction in the host's liver mass (and hence, energy stores). Experimental de-worming thus revealed pathological and immunological costs of the presence of lungworms, and of their removal by anthelmintic injection. Graphical abstract: Image 1 Highlights: Minor short-term immune responses to anthelmintics and lungworm decomposition. Long-term lungworm infection saw minor pathological impacts on lung/colon tissue. Heavier infection intensity saw increased whole blood phagocytic ability. Heavier infection intensity associated with reduction in liver mass (energy stores). De-worming revealed pathological costs of infection and anthelmintic treatment.